Discovery of Rickettsia spp. in mosquitoes collected in Georgia by metagenomics analysis and molecular characterization - Pollio, Adam R.; Jiang, Ju; Lee, Sam S.; Gandhi, Jaykumar S.; Knott, Brian D.; Chunashvili, Tamar; Conte, Matthew A.; Walls, Shannon D.; Hulseberg, Christine E.; Farris, Christina M.; Reinbold-Wasson, Drew D.; Hang, Jun (Frontiers in Microbiology, 2022)
Arthropods have a broad and expanding worldwide presence and can transmit a variety of viral, bacterial, and parasite pathogens. A number of Rickettsia and Orientia species associated with ticks, fleas, lice, and mites have been detected in, or isolated from, patients with febrile illness and/or animal reservoirs throughout the world. Mosquitoes are not currently considered vectors for Rickettsia spp. pathogens to humans or to animals. In this study, we conducted a random metagenome next-generation sequencing (NGS) of 475 pools of Aedes, Culex, and Culiseta species of mosquitoes collected in Georgia from 2018 to 2019, identifying rickettsial gene sequences in 33 pools of mosquitoes. We further confirmed the findings of the Rickettsia by genus-specific quantitative PCR (qPCR) and multi-locus sequence typing (MLST). The NGS and MLST results indicate that Rickettsia spp. are closely related to Rickettsia bellii, which is not known to be pathogenic in humans. The results, together with other reports of Rickettsia spp. in mosquitoes and the susceptibility and transmissibility experiments, suggest that mosquitoes may play a role in the transmission cycle of Rickettsia spp.